Contesting 'Race' and Sport Shaming the Colour Line - Hylton, Kevin (Taylor & Francis, 2018)
"In the decade since Kevin Hylton's seminal book 'Race' and Sport: Critical Race Theory was published, racialised issues have remained at the forefront of sport and leisure studies. In this important new book, Hylton draws on original research in contemporary contexts, from sport coaching to cyberspace, to show once again that Critical Race Theory is an insightful and productive tool for interrogating problematic social phenomena. Inspired by W.E.B. Du Bois' statement that ""the problem of the twentieth century is the problem of the colour line"", this book sheds a critical light on the way sport perpetuates racism, while identifying opportunities to challenge its insidious presence. Exploring and explaining the ways in which notions of 'race' are expressed and contested at individual, institutional and societal levels, it addresses key topics such as whiteness, diversity, colourblindness, unconscious bias, identity, leadership, humour and discourse to investigate how language can be used as a device for resistance against racism in sport. Contesting 'Race' and Sport: Shaming the Colour Line is vital reading for all sport studies students, academics and those with an interest in race, ethnicity and society."